(untitled) (Tanzania Journal for Population studies and Development, 2014)
This article seeks to understand risk sexual behaviours associated with HIV transmission among university undergraduate students in Tanzania. This analysis is based on 1119 sexually active never-married students (674 males and 445 females).The results show that 27% of university students (37.8% males and 21.3% females) had sexual intercourse with two or more sexual partners in the past 12 months. More male students than female students tended to have non-regular sexual partners (28% males and 17% females); and commercial sexual partners (6.5% males and 2.9% females). At the same time, condom use at higher-risk sexual intercourse is relatively low (46.0% males and 35.5% females). This is over and above the national average for the same age range. The difference by gender was statistically significant except for condom use at higher-risk sex. In addition, age, duration of stay at the university and staying at university facility or not were tested for their statistical significance to involvement in high-risk sexual behaviours. The article concludes that relatively high prevalence of higher-risk sexual behaviours among university students stems from inadequate attention to the notions of masculinity and femininity, which blurs the efforts that have already been obtained on HIV and AIDS interventions. Thus, there is urgent need to intensify HIV and AIDS related interventions among the university community to create awareness of higher-risk sexual behaviours. Further studies could explore the social and cultural contexts that bring about the observed gender differences in high-risk sexual behaviour among male and female university students.